IMPLEMENTATION OF PPH 21 POLICY DURING THE PANDEMIC COVID-19: IMPLEMENTASI KEBIJAKAN PPH 21 SAAT PANDEMI COVID-19 - Dini Vientiany; Salsabila Sofiya Wardani; Popi Dea Ananda; Elvira Andriyani (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The aim of this research is to analyze the implementation of the PPH 21 policy during the COVID-19 pandemic and find out how this policy affects the economy and society. This research uses a qualitative approach with library research or document analysis methods. A qualitative approach was chosen because this research aims to understand and interpret the meaning of the implementation of the PPH 21 policy and its impact on the economy and society. The library research method was chosen because the data needed for this research can be obtained from various document sources, such as books, scientific journals, news articles, official government reports, and trusted websites. Based on all the analysis results, it can be concluded that the implementation of PPh 21 during the Covid-19 pandemic has had a significant impact on tax revenues, taxpayer compliance, and economic and social conditions. The decline in PPh 21 revenues occurred because many taxpayers experienced a decrease in income and layoffs. However, the tax incentive policy implemented by the government has succeeded in increasing individual taxpayer compliance. The economic and social impacts of this policy are also diverse, with increasing people's purchasing power and assistance for MSMEs on the one hand, but also increasing income inequality and injustice for workers in the informal sector on the other.